Unsaturated fatty acid-associated lipid oxidation contributes to browning and flavor formation in high-temperature Daqu - Meina Jiang; Pingyan Cheng; Kaiping He; Min Zhong; Zhen Pang; Yinzhuo Yan; Diqiang Wang; Yansong Xue; Bei-Zhong Han (Food Chemistry, 2026)

Residential greenness and incident type 2 diabetes: A large prospective cohort study in China integrating evidence from 17 global cohorts - Jian-Cheng Jiang; Chuan-Jiang He; Ai-Min Xu; Lu Wang; Xiao-Qi Zhu; Bei-Bei Li; Wen Liu; Ya Qiu; Jing-Ran Xu; Min-Hui Li; Zhuo-Hao Wang; Xiao-Guang Zou; et al. (Environmental Research, 2026)

Gravity-assisted dual-mode biosensor based on CbAgo-driven gel-sol transition of DNA hydrogels for Salmonella detection - Jing-bo Jiao; Cheng-long Zhao; Bei-bei Tian; Jiang-li Cao; Qing Kang; Li-jun Wang; Nan Wang; Xin-jun Du; Shuo Wang (Chemical Engineering Journal, 2026)

Study on pipeline structural integrity and wear mechanism during horizontal directional drilling pullback of submarine pipelines - Yungen He; Wang Jian; Yuqi Zhang; Minke Huang; Yanchuan Cheng; Bei Jiang; Ming Chen; Kehan Chen; Wei Lu; Rongsheng Lin (Marine Georesources & Geotechnology, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Worker exposure to bioaerosols from sludge dewatering facilities: risks and mitigations - Bei-bei Cui; Wajid Ali; Wei-di Wan; Yi-ning Hu; Si-yi Liu; Tian-nuo Lai; Yong-tang Yan; Zhen Hu; Ting-xu Jin; Xiang Li; Zaheer Ahmad Nasir; Frederic Coulon; et al. (Water Research, 2026)

Gradient-explicit assessment of surface urban heat island intensity in subtropical megacities - Zilang Cheng; Qinshan Li; Siyu Zhou; Qianyi Bei; Zhuoyan Lin; Hongzhang Lin; Jing Xie; Desheng Xue (Sustainable Cities and Society, 2026)

Molecularly engineered water oxidation sites in D–A conjugated polymers for efficient H2O2 photosynthesis in pure water - Chengming Li; Wang Wang; Jingzhao Cheng; Sijie Wan; Guoqiang Luo; Bei Cheng; Jingsan Xu; Shaowen Cao (Science Bulletin, 2026)

Unraveling lithium occurrence in coal gangue through combined experimental and DFT Investigation - Yu Xie; Zhengwei Han; Jinhe Pan; Bei Miao; Cheng Liu; Changchun Zhou (Fuel, 2026)

Removal of hexavalent chromium from water using sulfidated nanoscale zero-valent iron: Regeneration and freeze–thaw stability, mechanism, and plant ecotoxicity - Wei Yuzhen; Cheng Aobo; Liu Bei; Ma Jushan; Muhammad Hamdan Rashid; Yu Jialu; Fasih Ullah Haider; Ma Shengyuan; Zhang Qinhu; Chu Run (Journal of Water Process Engineering, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Counteracting the Trojan horse effect: Dual-light-driven biochar/LaFeO3/TiO2 for synchronous ARGs-inactivation and phosphorus-adsorption - Bei Yang; Peifang Wang; Hao Liu; Lisha Wang; Shiying He; ShaoPeng Rong; Zhenkun Ma; Yueqin Cheng; Yanfang Feng; Lihong Xue (Chemical Engineering Journal, 2026)

Development and Evaluation of Antioxidant Postbiotics from Bacillus amyloliquefaciens C-1 to Alleviate DSS-Induced Colitis - Xinyao Hou; Jiayu Feng; Jiale Qin; Jianhui Mo; Rong Yu; Jia Lv; Shaoru Li; Jing Tian; Yue Cheng; Bei Han (Probiotics and Antimicrobial Proteins, 2026)

Microscopic insights into the fading mechanism of the hydrate memory effect - Liwei Cheng; Runze He; Jinlong Cui; Qun Yi; Bei Liu; Guangjin Chen (Fuel, 2026)

A carbon sink calculation model for concrete buildings considering time-variant environment - Jia-cheng Xu; Bei Li; Ye Tian; Ruo-yi Zhao; Guo-yi Zhang; Qiang Zeng; Cong-cong Ma; Bo-Tao Huang; Hong-jing Xue; Yun-jian Li; Qing Cai (Environmental Impact Assessment Review, 2026)

Advancing plant-based fat substitutes: structural, flavor, and color strategies for 3D/4D printing applications - Cheng-Zhen Nie; Ji Wang; Xu-Hui Huang; Bei-Wei Zhu; Lei Qin (Food Chemistry, 2025)

Texture and flavor switchable emulsion gels for replaced fat with improved mouthfeel and aromatic characteristics - Cheng-Zhen Nie; Yao Li; Ji Wang; Xu-Hui Huang; Bei-Wei Zhu; Lei Qin (Food Chemistry, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Cellular indexing of transcriptomes and epitopes by sequencing unveils coordinated RNA and protein landscape in ovary at single-cell resolution - Yujuan Qi; Yuxuan Feng; Xiaoyan Liu; Jiaxin Li; Qiuru Huang; Zhenbei Li; Sen Zheng; Ning Chen; Jie Cheng; Xinhui Yang; Wei Tao; Xiangnan Cao; et al. (Chemical Engineering Journal, 2025)

Effects of Haematococcus pluvialis on the physicochemical properties, flavor profile and antioxidant capacity of Baijiu - Hao Cheng; Wei-Cheng Xu; Yi Liu; Bei-Bei Hu; Cheng-Long Yang; Xiu-Lan Xie; Zhan-Ke Qin; Zi-Ai Deng; Hao-Jie Zhang; Qi Wang; Mao-Zhi Ren (Algal Research, 2025)

Coagulation enhancing the formation of aerobic granules in low-strength wastewater - Cheng Zeng; Linan Yu; Haoran Xu; Yuanyuan Cheng; Long Cheng; Lingcong Zeng; Shaoqin Li; Bei Long (Journal of Water Process Engineering, 2025)

Estimating the overlooked contribution of adsorption effects on CH4 release in wetland soils using a reactive transport model - Cheng Bei; Peng Liao; Kai Yu; Zhenqing Shi; Rong Li (Journal of Hydrology, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Modeling of carbon sink for concrete structures: From hydration kinetics to climate-driven carbonation - Ye Tian; Jia-Cheng Xu; Guo-Yi Zhang; Zu-Shi Tian; Bei Li; Ruo-Yi Zhao; Qiang Zeng; Bo-Tao Huang; Dong-Ming Yan (Sustainable Chemistry and Pharmacy, 2025)

Zoning and spatial resilience: Land use and food security in the Ili River Valley, China - Jinhua Wu; Hongwei Wang; Can Wang; Xin Huang; Jianxin Wei; Zhenggang Wang; Chi Zhang; Bei Chen; Yilinuer Yiming; Cheng Lei; Chunshan Zhou (Land Use Policy, 2025)

Structure from motion-convolutional neural network model (SfM-CNN) achieved accurate portable Chinese dietary chemical composition estimation for dietary recall - Peihua Ma; Hsuan Chih Hong; Xiaoxue Jia; Cheng Jan Chi; Ning Xiao; Bei Fan; Fengzhong Wang; Cheng-I Wei (Food Chemistry, 2025)

Antibiotic Susceptibility Evaluation in Bacterial Infections from Orthopedic Inpatients with Leg Trauma - Juanjuan Zhang; Fangfang Jiao; Yonghan Ge; Bei Cheng; Jingjing Guo (Current Microbiology, 2025)

Gestational exposure to micro- and nanoplastics leads to poor pregnancy outcomes by impairing placental trophoblast syncytialization - Yanmin Cheng; Yue Li; Yulu Zhang; Hui Liu; Bei Yang; Jun Zhu; Haibin Kuang (Environmental Pollution, 2025)

MTGGF: A Metabolism Type-Aware Graph Generative Model for Molecular Metabolite Prediction - Peng-Cheng Zhao; Xue-Xin Wei; Qiong Wang; Hao-Yang Wang; Bing-Xue Du; Jia-Ning Li; Bei Zhu; Hui Yu; Jian-Yu Shi (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Process and mechanism of extracting valuable metals from spent lithium-ion batteries with a mixed organic acid - Hua Long; He-yu Xu; Cheng-bin Mao; Bei Wang; Jun-na Xu; Jie Zhu; Ya-yun Ma (Process Safety and Environmental Protection, 2025)

SWAT model application for calculating ecological flow in sub-basins of the Huangshui River Basin - Xue Fang; Weijun He; FaGuang Wen; Min An; Bei Wang; Boxuan Cheng (Journal of Environmental Management, 2025)

Transient chemical-mediated epigenetic modulation confers unrestricted lineage potential on human primed pluripotent stem cells - Shi Chen; Yuanyuan He; Lejun Lv; Bei Liu; Cheng Li; Hongkui Deng; Jun Xu (Science China Life Sciences, 2025)

Immunofluorescent analysis of exosomes using a microchip filled with transparent antibody-conjugated beads for breast cancer liquid biopsy - Na Li; Cheng Cheng; Di Wu; Zixuan Song; Bei Wang; Guiying Li; Fang Yang (Analytica Chimica Acta, 2025)

Mechanochemically coordinating Fe-tannic acid towards the fabrication of highly-microporous carbon as advanced supercapacitor electrode - Yue Liu; Bei Cheng; Xingyan Xie; Jian Chen; Liu Wan; Cheng Du; Yan Zhang; Mingjiang Xie (Fuel, 2025)

An efficient, high-throughput enrichment system for the rapid detection of E. coli at low concentrations in water - Binghuan He; Fangzhou Zhang; Pengfei Gong; Rui Sun; Jianxin Cheng; Chenghui Jin; Bo Liu; Jianlong Zhao; Shilun Feng; Bei Li (Analytica Chimica Acta, 2025)

The effects of influent 5-Deoxystrigol concentrations on integral biogas upgrading and nutrient removal by different algal-fungal-bacterial consortium - Pu Cheng; Huayun Yang; Zhengfang Wang; Chunzhi Zhao; Bei Lu; Hui Zhang; Yongjun Zhao (Algal Research, 2024)

PM2.5 constituents associated with mortality and kidney failure in childhood-onset lupus nephritis: A 19-year cohort study - Guohua He; Yaqi Wang; Cheng Cheng; Jianhui Guo; Zhilang Lin; Ziyun Liang; Bei Jin; Liyuan Tao; Liping Rong; Lizhi Chen; Tianxin Lin; Yining Hua; et al. (Science of The Total Environment, 2024)

Isolation and characterization of Bifidobacterium spp. from breast milk with different human milk oligosaccharides utilization and anti-inflammatory capacity - Xinxin Ma; Jianhui Mo; Lu Shi; Yue Cheng; Jiayu Feng; Jiale Qin; Wanghong Su; Jia Lv; Shaoru Li; Qiang Li; Hui Tan; Bei Han (Food Research International, 2024)

Solvent-free mechanochemical synthesis of Mg-gallic acid complex for the fabrication of high-performance supercapacitor porous carbon - Bei Cheng; Beina Yang; Xingyan Xie; Liu Wan; Jian Chen; Cheng Du; Yan Zhang; Mingjiang Xie (Chemical Engineering Journal, 2024)

Deciphering the pivotal material properties of perovskite for hydrogen production in tar catalytic cracking - Wang-mi Chen; Bei-dou Xi; Mei-ying Ye; Ming-xiao Li; Jia-qi Hou; Yu-fang Wei; Cheng-ze Yu; Fan-hua Meng (Fuel, 2024)

Multi-scenario application of chitosan emulsions as fat replacers: Based on the regulation of chitosan hydrophobicity and emulsion rheological properties - Cheng-Zhen Nie; Yao Li; Xu-Hui Huang; Hao-Peng Wang; Xu-Song Wang; Xiu-Ping Dong; Bei-Wei Zhu; Lei Qin (Food Hydrocolloids, 2024)

Disulfidptosis: A new type of cell death - Fei Xiao; Hui-Li Li; Bei Yang; Hao Che; Fei Xu; Gang Li; Cheng-Hui Zhou; Sheng Wang (Apoptosis, 2024)
Disulfidptosis is a novel form of cell death that is distinguishable from established programmed cell death pathways such as apoptosis, pyroptosis, autophagy, ferroptosis, and oxeiptosis. This process is characterized by the rapid depletion of nicotinamide adenine dinucleotide phosphate (NADPH) in cells and high expression of solute carrier family 7 member 11 (SLC7A11) during glucose starvation, resulting in abnormal cystine accumulation, which subsequently induces andabnormal disulfide bond formation in actin cytoskeleton proteins, culminating in actin network collapse and disulfidptosis. This review aimed to summarize the underlying mechanisms, influencing factors, comparisons with traditional cell death pathways, associations with related diseases, application prospects, and future research directions related to disulfidptosis.

Three-dimensional Ni foam supported Pt/NiFe LDH catalyst with enhanced oxygen activation for room-temperature formaldehyde oxidation - Jiawei Ye; Min Wu; Bicheng Zhu; Bei Cheng; Jiaguo Yu (Journal of Hazardous Materials, 2024)

Effects of mixed LED light wavelengths and strigolactone analog concentrations on integral biogas upgrading and antibiotic removal from piggery wastewater by different microalgae-bacteria-fungi consortia - Pu Cheng; Zhengfang Wang; Bei Lu; Yongjun Zhao; Hui Zhang (Algal Research, 2024)

Endogenous iron-enriched biochar derived from steel mill wastewater sludge for tetracycline removal: Heavy metals stabilization, adsorption performance and mechanism - Lu Zhou; Guanhao Zhang; Yulin Zeng; Xunli Bao; Bei Liu; Liang Cheng (Chemosphere, 2024)

Swelling characteristics of compacted graphene-modified GMZ bentonite infiltrated with NaCl solution - Yu-Hao Hu; Yong-Gui Chen; Yu-Cheng Li; Wei-Min Ye; Qiong Wang; Dong-Bei Wu (Bulletin of Engineering Geology and the Environment, 2024)

A New Perspective on the Semi-quantitative Meso-structural Failure Mechanism of Deep Weak Interlayer Zone Under Different Stress Paths - Shu-Qian Duan; Po Gao; Ding-Ping Xu; Bei Cao; Guo-feng Liu; Quan Jiang; Shi-Li Qiu; Jie-Cheng Xiong (Rock Mechanics and Rock Engineering, 2024)

Short-term effects of exposure to cold spells on blood pressure among adults in Nanjing, China - Tian-Lin Li; Bei-Jing Cheng; Nan Jiang; Xing-Chen Meng; Chun Wang; Yang Huang; Ke Meng; Hui Li; Xin-Yi Zhu; Ran Liu (Air Quality, Atmosphere & Health, 2024)

Potential Impact of Hypoxic Astrocytes on the Aggravation of Depressive Symptoms in Parkinson’s Disease - Yue Peng; Jiali He; Hongling Xiang; Lei Xie; Jin She; Donghui Cheng; Bei Liu; Jing Hu; Hao Qian (Journal of Molecular Neuroscience, 2024)

Distinct resting-state functional connectivity of the anterior cingulate cortex subregions in first-episode schizophrenia - Huan Huang; Cheng Chen; Bei Rong; Yuan Zhou; Wei Yuan; Yunlong Peng; Zhongchun Liu; Gaohua Wang; Huiling Wang (Brain Imaging and Behavior, 2024)

Sustainable, efficient, and synergistic photocatalytic degradation toward organic dyes and formaldehyde gas via Cu2O NPs@wood - Lingling Wang; Maojie Tang; Haiqiu Jiang; Jiahui Dai; Ruifeng Cheng; Bei Luo; Long Yang; Guanben Du; Wei Gao (Journal of Environmental Management, 2024)

Molecular simulation study on carbon dioxide replacement in methane hydrate near the freezing point - Liwei Cheng; Yunfei Li; Jinlong Cui; Qi Wu; Bei Liu; Fulong Ning; Guangjin Chen (Gas Science and Engineering, 2024)

Effects of dietary betaine supplementation on growth performance, feed intake, intestinal histology, lipid metabolism, and immune response of black tiger shrimp (Penaeus monodon) fed diets containing two levels of raw feed attractants - Gui-Lun He; Meng-Lin Shi; Yu-Cheng Liu; Liu-Tong Chen; Xin Chen; Wen-Bo Zhu; Zheng-Bang Chen; Bei-Ping Tan; Shi-Wei Xie (Aquaculture International, 2024)

Spatial-temporal variation of soil organic matter decomposition potential in China - Qi Chen; Zeyan Zhou; Sulin Cai; Meiqi Lv; Yinghui Yang; Yunchao Luo; Han Jiang; Run Liu; Tingting Cao; Bei Yao; Yunru Chen; Qiang Li; et al. (Soil and Tillage Research, 2024)

Air particulate pollution exposure associated with impaired cognition via microbiota gut-brain axis: an evidence from rural elderly female in northwest China - Jia Yuan; Hui Tan; Yue Cheng; Xinxin Ma; Sijin Jiang; Xinyao Hou; Shaoru Li; Lu Shi; Pu Li; Hongmei Xu; Jia Lv; Bei Han (Environmental Science and Pollution Research, 2023)

Algal-bacterial granular sludge for simultaneous denitrification and yttrium removal - Zhenghao Li; Yuanyuan Cheng; Mingjing Zeng; Yi Luo; Yiran Hou; Junfeng Wu; Bei Long (Journal of Environmental Chemical Engineering, 2023)

Effects of PM2.5 emissions from household fuel combustion on biomarkers and pulmonary function in rural areas of Fenwei Plain, China - Rong Feng; Hongmei Xu; Hongwei Lu; Bei Han; Yue Cheng; Yunxuan Gu; Jian Sun; Liu Yang; Zhenxing Shen; Junji Cao (Atmospheric Pollution Research, 2023)

A study on carbon dioxide emissions of high-polymer road maintenance technology based on life cycle assessment evaluation - Yanhui Zhong; Shengjie Xu; Bei Zhang; Haoyuan Cheng; Mengxian Wang; Yongding Niu; Runyang Li (Journal of Cleaner Production, 2023)

Bifunctional CdS/COF S-scheme photocatalyst for enhanced H2 evolution and organic synthesis - Guotai Sun; Jianjun Zhang; Bei Cheng; Huogen Yu; Jiaguo Yu; Jingsan Xu (Chemical Engineering Journal, 2023)

Associating phthalate exposure during pregnancy with preschooler's FMI, ABSI and BRI trajectories via putative mechanism pathways - Hui Gao; Yi Zhang; Li-wen Chen; Hong Gan; Meng-juan Lu; Binbin Huang; Juan Tong; Meng-long Geng; Kun Huang; Cheng Zhang; Bei-bei Zhu; Shan-shan Shao; et al. (Chemosphere, 2023)

Serum levels of IL-6/IL-10/GLDH may be early recognition markers of anti-tuberculosis drugs (ATB) -induced liver injury - Huai-Rong Xiang; Yun Li; Xuan Cheng; Bei He; Hua-Min Li; Qi-Zhi Zhang; Bin Wang; Wen-Xing Peng (Toxicology and Applied Pharmacology, 2023)

Short-term effects of cold spells on hematocrit among adults in Nanjing, China: A distributed-lagged effect analysis - Bei-Jing Cheng; Tian-Lin Li; Hui Li; Ke Meng; Xing-Chen Meng; Jia Wang; Chun Wang; Lin-Sheng Yang; Xin-Yi Zhu; Ran Liu (Science of The Total Environment, 2023)

Coupling of microplastic contamination in organisms and the environment: Evidence from the tidal flat ecosystem of Hangzhou Bay, China - Xinyi Cai; Huili Chen; Jie Cheng; Bei Huang; Binsong Jin; Jianbo Lu (Journal of Hazardous Materials, 2023)

Low ambient temperature increases the risk and burden of atrial fibrillation episodes: A nationwide case-crossover study in 322 Chinese cities - Xinlei Zhu; Renjie Chen; Yong Zhang; Jialu Hu; Yixuan Jiang; Kai Huang; Jianan Wang; Wei Li; Bei Shi; Yundai Chen; Lang Li; Bao Li; et al. (Science of The Total Environment, 2023)

Optimal allocation of water pollutant discharge permits based on Environmental Gini Coefficient (EGC): a case study of Qinhuai river basin in Nanjing, China - Bei Guan; Xiuqiong Liang; Yang Yang; Xiang Sun; Jiawei Wang; Danyi Wei; Bin Wang; Han Cheng (Environment, Development and Sustainability, 2023)

Combined effects of prenatal phthalate exposure on cardiometabolic risk score among 4- to 7-year-old children: MABC study - Hui Gao; Meng-long Geng; Juan Tong; Bao-lin Wang; Kun Huang; Yi Zhang; Hong Gan; Bei-bei Zhu; Peng Ding; Qu-nan Wang; Jian-qing Wang; Cheng Zhang; et al. (Chemosphere, 2023)

Associations of personal exposure to domestic heating and cooking fuel emissions and epidemiological effects on rural residents in the Fenwei Plain, China - Yunxuan Gu; Hongmei Xu; Rong Feng; Yue Cheng; Bei Han; Kin Fai Ho; Zexuan Wang; Yansu He; Linli Qu; Steven Sai Hang Ho; Jian Sun; Zhenxing Shen; et al. (Science of The Total Environment, 2023)

Salt Bridge-intermediated three phase decoupling electrolytes for high voltage electrolytic aqueous Zinc-Manganese dioxides battery - Qi Xu; Qi-Xing Xie; Tong Xue; Gao Cheng; Jian-Dong Wu; Lan Ning; Xiang-Hui Yan; You-Jun Lu; Zhong-Li Zou; Bei-Ping Wang; Feng-Lan Han (Chemical Engineering Journal, 2023)

Selenium attenuates the association of co-exposure to arsenic, cadmium, and lead with cognitive function among Chinese community-dwelling older adults - Bei-Jing Cheng; Jie Sheng; Hong-Li Wang; Yuan Wang; Hong-Juan Cao; Xiu-De Li; Ting-Ting Zhou; Xiang-Long Meng; Huan-Huan Nie; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; et al. (Environmental Science and Pollution Research, 2022)

The association between essential trace element mixture and atherosclerotic cardiovascular disease risk among Chinese community-dwelling older adults - Xiang-long Meng; Yuan Wang; Hong-li Wang; Huan-huan Nie; Bei-jing Cheng; Hong-juan Cao; Xiu-de Li; Su-fang Wang; Gui-mei Chen; Fang-biao Tao; Jie Sheng; Lin-sheng Yang (Environmental Science and Pollution Research, 2022)

Characteristics of the microbiota and metabolic profile of high-temperature Daqu with different grades - Yuandi Zhang; Fang Ding; Yi Shen; Wei Cheng; Yansong Xue; Bei-Zhong Han; Xiaoxue Chen (World Journal of Microbiology and Biotechnology, 2022)

Impact of the evolution of Plateau Lake landscape pattern on ecosystem service value in the Pearl River basin: a case study of Yilong Lake Basin in Yunnan Province, China - Guoqiang Ma; Jianping Xiao; Qiujie Li; Lixun Zhang; Bei An; Guojun Sun; Hua Cheng; Jiaqi Tang; Hong Li (Acta Geophysica, 2022)

Programmed Death-1 Deficiency Aggravates Motor Dysfunction in MPTP Model of Parkinson's Disease by Inducing Microglial Activation and Neuroinflammation in Mice - Ying-Ying Cheng; Bei-Yu Chen; Gan-Lan Bian; Yin-Xiu Ding; Liang-Wei Chen (Molecular Neurobiology, 2022)

Alantolactone exhibits antiproliferative and apoptosis-promoting properties in colon cancer model via activation of the MAPK-JNK/c-Jun signaling pathway - Yijing Ren; Cheng Lv; Jing Zhang; Beibei Zhang; Bei Yue; Xiaoping Luo; Zhilun Yu; Hao Wang; Junyu Ren; Zhengtao Wang; Wei Dou (Molecular and Cellular Biochemistry, 2021)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Genetic Analysis of Prosaposin, the Lysosomal Storage Disorder Gene in Parkinson’s Disease - Yong-Ping Chen; Xiao-Jing Gu; Ru-Wei Ou; Ling-Yu Zhang; Yan-Bing Hou; Kun-Cheng Liu; Bei Cao; Qian-Qian Wei; Wei Song; Bi Zhao; Ying Wu; Jing-Qiu Cheng; et al. (Molecular Neurobiology, 2021)

Use of a Multi-Objective Correlation Index to Analyze the Power Generation, Water Supply and Ecological Flow Mutual Feedback Relationship of a Reservoir - Zhenhui Wu; Yadong Mei; Bei Cheng; Tiesong Hu (Water Resources Management, 2021)

Effects of Different Component Contents of Colistin Methanesulfonate on the Pharmacokinetics of Prodrug and Formed Colistin in Human - Ya-Xin Fan; Yuan-Cheng Chen; Yi Li; Ji-Cheng Yu; Xing-Chen Bian; Xin Li; Wan-Zhen Li; Bei-Ning Guo; Hai-Lan Wu; Xiao-Fen Liu; Yu Wang; Xiao-Yong Xu; et al. (Pharmaceutical Research, 2021)

Probiotic and Safety Properties Screening of Enterococcus faecalis from Healthy Chinese Infants - Juan Wang; Rong Da; Xiaohong Tuo; Yue Cheng; Jie Wei; Kaichong Jiang; Jia Lv; Omolade Monisayo Adediji; Bei Han (Probiotics and Antimicrobial Proteins, 2020)

Identification and countermeasures of limiting factors of regional sustainable development: a case study in the Pearl River Delta of China - Zhao-Tian Li; Meng-Meng Hu; Miao Li; Meng-Yu Jiao; Bei-Cheng Xia (Environment, Development and Sustainability, 2020)

Baeckeins L and M, two novel C -methylated triflavonoids from the roots of Baeckea frutescens L. - Cheng-Jun Jia; Xiao-Min Sun; Xiang-Yun Zhang; Zi-Jiao Wei; Bei-Xi Jia (Natural Product Research, 2020)

Selection of reliable reference genes for gene expression studies in Caenorhabditis elegans exposed to crystals (Cry1Ia36) protein of Bacillus thuringiensis - Dongwei Wang; Yong Liu; Deyong Zhang; Qingcong He; Bei Tang; Feixue Cheng (Molecular Biology Reports, 2019)

Investigation of factors affecting the gaseous and particulate matter emissions from diesel vehicles - Bei Wang; Yik-Sze Lau; Yuhan Huang; Bruce Organ; Shun-Cheng Lee; Kin-Fai Ho (Air Quality, Atmosphere & Health, 2019)

Selenium (Se) Does Not Reduce Cadmium (Cd) Uptake and Translocation in Rice (Oryza sativa L.) in Naturally Occurred Se-Rich Paddy Fields with a High Geological Background of Cd - Bei-Bei Yang; Cheng Yang; Zong-Yuan Shao; Hao Wang; Shu-Ting Zan; Meng Zhu; Shou-Biao Zhou; Ru-Yi Yang (Bulletin of Environmental Contamination and Toxicology, 2019)

Correction to: Past Millennium Contrasting Hydroclimate Patterns Between Monsoonal Northern China and Arid Central Asia: a Modeling Study - Youbing Peng; Hai Cheng; Caiming Shen; Ying Xu; Naifang Bei (Asia-Pacific Journal of Atmospheric Sciences, 2019)

Past Millennium Contrasting Hydroclimate Patterns Between Monsoonal Northern China and Arid Central Asia: a Modeling Study - Youbing Peng; Hai Cheng; Caiming Shen; Ying Xu; Naifang Bei (Asia-Pacific Journal of Atmospheric Sciences, 2018)

MicroRNA-486-5p suppresses TGF-β2-induced proliferation, invasion and epithelial–mesenchymal transition of lens epithelial cells by targeting Smad2 - Bei Liu; Jianhua Sun; Xiaoqin Lei; Zhongqiao Zhu; Cheng Pei; Li Qin (Journal of Biosciences, 2017)

Cloning of the ANT gene and its expression profiles at different developmental stages and post-molting times in the ridgetail white prawn Exopalaemon carinicauda - Huan Gao; Bei Xue; Lian Zhao; Xiaofang Lai; Binlun Yan; Hanliang Cheng; Qian Pan (Fisheries Science, 2017)

Cancer risk from gaseous carbonyl compounds in indoor environment generated from household coal combustion in Xuanwei, China - Ka-Hei Lui; Wen-Ting Dai; Chi-Sing Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Bei Wang; Jinwen Li; Jun-Ji Cao; Shun-Cheng Lee; Kin-Fai Ho (Environmental Science and Pollution Research, 2017)

Influence of Selenium on the Production of T-2 Toxin by Fusarium poae - Bolun Cheng; Yan Zhang; Bei Tong; Hong Yin (Biological Trace Element Research, 2017)

Observation and modeling on irregular purple soil water infiltration process - Dong-bing Cheng; Lin-yao Dong; Feng Qian; Bei Sun (Journal of Mountain Science, 2017)

Prognostic value of human papillomavirus 16/18 genotyping in low-grade cervical lesions preceded by mildly abnormal cytology - Jing Ye; Bei Cheng; Yi-fan Cheng; Ye-li Yao; Xing Xie; Wei-guo Lu; Xiao-dong Cheng (Journal of Zhejiang University-SCIENCE B, 2017)

Human papillomavirus (HPV) E6/E7 mRNA detection in cervical exfoliated cells: a potential triage for HPV-positive women - Ye-li Yao; Qi-fang Tian; Bei Cheng; Yi-fan Cheng; Jing Ye; Wei-guo Lu (Journal of Zhejiang University-SCIENCE B, 2017)

Identification and characterization of Phytopythium helicoides causing stem rot of Shatangju mandarin seedlings in China - Xiao-Ren Chen; Bei-Bei Liu; Yu-Ping Xing; Bao-Ping Cheng; Mei-Ling Liu; Yun-Hui Tong; Jing-You Xu (European Journal of Plant Pathology, 2016)

Peripheral Blood MicroRNA Expression Profiles in Alzheimer’s Disease: Screening, Validation, Association with Clinical Phenotype and Implications for Molecular Mechanism - Ru-Jing Ren; Yong-Fang Zhang; Eric B. Dammer; Yi Zhou; Li-ling Wang; Xiao-Hong Liu; Bei-Lei Feng; Guo-Xin Jiang; Sheng-Di Chen; Gang Wang; Qi Cheng (Molecular Neurobiology, 2016)

Physiological and biochemical characterization of sheepgrass (Leymus chinensis) reveals insights into photosynthetic apparatus coping with low-phosphate stress conditions - Lingyu Li; Haomeng Yang; Weibo Ren; Bei Liu; Dongmei Cheng; Xinhong Wu; Jirui Gong; Lianwei Peng; Fang Huang (Journal of Plant Biology, 2016)

The Effects of Molecular Properties on Ready Biodegradation of Aromatic Compounds in the OECD 301B CO2 Evolution Test - Mei He; Cheng-Fang Mei; Guo-Ping Sun; Hai-Bei Li; Lei Liu; Mei-Ying Xu (Archives of Environmental Contamination and Toxicology, 2016)

Factors Associated with Thrombolysis Outcome in Ischemic Stroke Patients with Atrial Fibrillation - Qiuyun Zhao; Xiaobo Li; Wanli Dong; Min Ye; Yongjun Cao; Meijuan Zhang; Qiantao Cheng; Junshan Zhou; Guofang Chen; Ming Yu; Shanshan Hong; Xiue Wei; et al. (Neuroscience Bulletin, 2016)

Serum amyloid A stimulates vascular endothelial growth factor receptor 2 expression and angiogenesis - Mei Lv; Yan-fei Xia; Bo Li; Hui Liu; Jin-yu Pan; Bei-bei Li; Cheng Zhang; Feng-shuang An (Journal of Physiology and Biochemistry, 2016)

Opposite Sex Contact and Isolation: A Novel Depression/Anxiety Model - Liu Yang; Li-Jun Shi; Bei Tang; Qiu-Qin Han; Jin Yu; Gen-Cheng Wu; Yu-Qiu Zhang (Neuroscience Bulletin, 2016)

Peperites in the Permian Tarim large igneous province in Northwest China and their constraints on the local eruption environments - Bei Zhu; ZhaoJie Guo; ZiYa Zhang; Feng Cheng (Science China Earth Sciences, 2014)

ABI-like transcription factor gene TaABL1 from wheat improves multiple abiotic stress tolerances in transgenic plants - Dong-Bei Xu; Shi-Qing Gao; You-Zhi Ma; Zhao-Shi Xu; Chang-Ping Zhao; Yi-Miao Tang; Xue-Yin Li; Lian-Cheng Li; Yao-Feng Chen; Ming Chen (Functional & Integrative Genomics, 2014)

Recombinant expression of different mutant K-ras gene in pancreatic cancer Bxpc-3 cells and its effects on chemotherapy sensitivity - TengFei Shao; YuanTing Zheng; Bei Zhao; Tao Li; KeGuang Cheng; WeiMin Cai (Science China Life Sciences, 2014)

A rapid thin-layer chromatography bioautographic method for detecting the monoamine oxidase inhibitors in plants - Ji-Bei Liang; Zhong-Duo Yang; Zong-Mei Shu; Cheng-Cheng Yu (Natural Product Research, 2014)

Purification and characterization of alkaline phosphatase from the gut of sea cucumber Stichopus japonicus - Hai-Tao Wu; Dong-Mei Li; Bei-Wei Zhu; Jing-Heng Cheng; Jin-Jian Sun; Feng-Lin Wang; Yang Yang; Yu-Kun Song; Chen-Xu Yu (Fisheries Science, 2013)

Expression of survivin and patients survival in non-small cell lung cancer: a meta-analysis of the published studies - Li-nian Huang; Dong-sheng Wang; Yu-qing Chen; Cheng-ling Zhao; Bei-lei Gong; An-bang Jiang; Wei Jia; Feng-dan Hu (Molecular Biology Reports, 2013)

Inhibition of hydrogen sulfide synthesis provides protection for severe acute pancreatitis rats via apoptosis pathway - Gang Wang; Bing Han; Haoxin Zhou; Linfeng Wu; Yongwei Wang; Guang Jia; Jiachen Lv; Zhuoxin Cheng; Shangha Pan; Ji Liu; Yinan Zhou; Bei Sun (Apoptosis, 2013)

Interacting Partners of AMPA-Type Glutamate Receptors - Juan Cheng; Jie Dong; Yaxuan Cui; Liecheng Wang; Bei Wu; Chen Zhang (Journal of Molecular Neuroscience, 2012)

Calibration of regional ionospheric delay with uncombined precise point positioning and accuracy assessment - LI WEI; CHENG PENGFEI; BEI JINZHONG; WEN HANJIANG; WANG HUA (Journal of Earth System Science, 2012)

Molecular characterization of β-lactam-resistant Escherichia coli isolated from Fu River, China - Li-Kou Zou; Li-Wen Li; Xin Pan; Guo-Bao Tian; Yan Luo; Qi Wu; Bei Li; Lin Cheng; Jiu-Jing Xiao; Su Hu; Yang Zhou; Yu-Juan Pang (World Journal of Microbiology and Biotechnology, 2012)

MicroRNA- 1 represses Cx43 expression in viral myocarditis - Hong-Fei Xu; Yu-Jie Ding; Yi-Wen Shen; Ai-Min Xue; Hong-Mei Xu; Cheng-Liang Luo; Bei-Xu Li; Yue-Lin Liu; Zi-Qin Zhao (Molecular and Cellular Biochemistry, 2012)

Induction of primitive pigment cell differentiation by visible light (helium–neon laser): a photoacceptor-specific response not replicable by UVB irradiation - Cheng-Che E. Lan; Shi-Bei Wu; Ching-Shuang Wu; Yi-Chun Shen; Tzu-Ying Chiang; Yau-Huei Wei; Hsin-Su Yu (Journal of Molecular Medicine, 2012)

Evolution of the Chloroplast trnL-trnF Region in the Gymnosperm Lineages Taxaceae and Cephalotaxaceae - Da Cheng Hao; Bei Li Huang; Shi Lin Chen; Jun Mu (Biochemical Genetics, 2009)

Production of Prnp −/− goats by gene targeting in adult fibroblasts - Caihong Zhu; Bei Li; Guohua Yu; Jianquan Chen; Huiqing Yu; Juan Chen; Xujun Xu; Youbing Wu; Aimin Zhang; Guoxiang Cheng (Transgenic Research, 2009)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)

Characterization and presynaptic modulation of stimulation-evoked exocytotic co-release of noradrenaline and neuropeptide Y in guinea pig heart - Markus Haass; Bei Cheng; Gert Richardt; Rudolf E. Lang; Albert Schmig (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)